2015
DOI: 10.1007/s12061-015-9160-4
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Land Conversion Drivers in Northeast Iran: Application of Structural Equation Model

Abstract: Agricultural Land Conversion (ALC) has been introduced as one of the most important factors affecting ecosystem. This type of conversion has led to several challenges in agricultural development and human life. Monitoring ALC plays a crucial role when dealing with such challenges. The main objective of this study was to monitor the trend of ALC in the Qazvin province located in Northwest Iran from 1990 to 2010 using remote sensing data. The results showed that 44,845 ha of agricultural lands (3.03% of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 60 publications
1
26
0
1
Order By: Relevance
“…In other words, the suitability of any land for any use should be determined primarily on physical criteria, secondarily on agronomic criteria, and finally, on socio-economic criteria. However, various studies [49][50][51][52][53][54][55][56][57][58] have shown that socio-economic factors and variables have always played an important role in land use change. In that case, although socio-economic factors and variables may not have a direct and important role on determining the suitability of lands for agriculture or other uses, through their impacts on land use and cover changes they do affect it.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the suitability of any land for any use should be determined primarily on physical criteria, secondarily on agronomic criteria, and finally, on socio-economic criteria. However, various studies [49][50][51][52][53][54][55][56][57][58] have shown that socio-economic factors and variables have always played an important role in land use change. In that case, although socio-economic factors and variables may not have a direct and important role on determining the suitability of lands for agriculture or other uses, through their impacts on land use and cover changes they do affect it.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is usually recommended to break down the variance of each factor into common and unique portions when the measured variables might have a linear function of the unmeasured variables [7,59]. The Kaiser-Meyer-Olkin (KMO) index was equal to 0.822.…”
Section: Factor Affecting the Impacts Of Rshsmentioning
confidence: 99%
“…In recent years, rural tourism has developed due to population growth, urbanization, the development of transportation and communication routes, economic growth, transferring capital, and the income and employment from industrial, urban, and developed areas to non-industrial regions [3][4][5][6][7][8]. In general, rural tourism is a developmental tool that is used to protect natural resources and can also affect the long-term growth of tourism without damaging the natural environment [7,[9][10][11]. In this context, rural second homes (RSHs) are considered as one of the main instruments of permanent…”
Section: Introductionmentioning
confidence: 99%
“…This process has intensified ALC. Apparently, so far not only have all the government policies and plans failed to control ALC, but some of them have exacerbated it [15].…”
Section: A Land Use Changes and Its Challengesmentioning
confidence: 99%